The United Kingdom and Ireland Association of Forensic Toxicologists; establishing best practice for professional training & development in forensic toxicology. Issue 1 (January 2017) - Cosbey, Simon; Elliott, Simon; Paterson, Sue
Abstract: The current status of forensic toxicology in the United Kingdom is discussed with an emphasis on professional training and development. Best practice is proposed using a blend of modular foundation knowledge training, continuing professional development, academic study, research & development and ongoing analytical practice. The need for establishing a professional career structure is also discussed along with a suggested example of a suitable model. The issues discussed in this paper are intended to provoke discussion within the forensic toxicology community, industry regulators and other government bodies responsible for the administration of justice. Highlights: Best practice for training and development in forensic toxicology is proposed. Includes a blend of foundation knowledge, CPD, academic study and ongoing practice The need for a professional career development structure is discussed.